PENERAPAN DESAIN KELAS EFEKTIF BAGI ANAK BERKEBUTUHAN KHUSUS DI SNETS YCHI AUTISM CENTRE CABANG JEPARA - Murni, Sri; Naiema, An Naas Shahifatun; Suhaila, Arina; Sanjali, Sarwan; Rizka, Muhammad Dany; Shofiyuddin, Muhammad; Zulfahmi, Muhammad Nofan (Jurnal Terapan Abdimas, 2022)
Abstract. In each child there is an ability or potential that is unique to him or her. And child rights which state that all children have the same rights and obligations to live and develop fully according to their potential. Autistic children generally have a high level of carefulness in terms of visualization. This sensitivity to visualization is traumatic to certain colors. the study room is designed according to the characteristics of the behavior of children with special needs or according to the type or type of therapy. "Form Follow Function" which means that the shape of the room follows its function, the interior design of the occupational class at the Jepara Branch of Snets Ychi Autism Center makes a positive contribution to achievement by increasing interest in learning. This positive contribution is obtained through the effects of using materials and colors on interior elements, anthropometry of indoor furniture, and lighting system. Nevertheless. The resources of educators at YCHI are not able to design and manage classrooms that are suitable for children with special needs. Thus, this enggagement program  is carried out by means of training and mentoring methods for educators in managing classrooms. The results of this program indicate an increase in the quality of classroom design that is suitable for children with special needs.Abstrak. Pada setiap anak memiliki kemampuan atau potensi diri yang unik dan berbeda-beda. Hak-hak anak (child right) memiliki hak dan kewajiban yang sama untuk mengembangkan potensinya. Anak autis, pada dasarnya memiliki kemampuan yang tinggi terkait dengan visualisasi. Kepekaan terhadap visualisasi ini menyebabkan adanya traumatis terhadap warna-warna tertentu. Ruang belajar didesain sesuai dengan karakteristik perilaku Anak Berkebutuhan Khusus yang sesuai dengan jenis atau macam terapinya. “Form Follow Function” yang artinya bahwa bentuk ruang mengikuti fungsinya, desain interior kelas okupasi di Snets YCHI Autism Centre Cabang Jepara memberikan kontribusi yang positif dalam pencapaian dengan meningkatkan minat belajar. Kontribusi positif tersebut didapatkan melalui pengaruh-pengaruh yang ditimbulkan dari penggunaan bahan dan warna pada elemen interior, antropometri perabot dalam ruang dan sistem pencahayaan. Meski demikian. Sumberdaya para pendidik di YCHI belum memadai untuk mendesain dan mengelola ruang kelas yang sesuai untuk anak berkebutuhan khusus. Demikian, pengabdian ini dilaksanakan dengan metode pelatihan dan pendampingan bagi para pendidik dalam mengelola ruang kelas. Hasil program ini menunjukkan adanya peningkatan kualitas desain ruang kelas yang sesuai untuk anak berkebutuhan khusus.